Pharmacovigilance in veterinary profession - Fatih Doğan (Eurasian Journal of Veterinary Sciences)
Aim: The practising clinical veterinarians in Turkey were questioned about their opinions and experiences on adverse drug reactions. Materials and Methods: The research was applied on 250 clinic veterinarian who graduated from 13 different universities working in 22 different cities. It was expected that veterinarians shared their experiences in research, after pharmacovigilance was mentioned. Results: 81% of veterinarians had experienced at least one adverse drug reaction. When the drug groups were evaluated, most adverse drug reactions were determined (p<0.05) in vitamin-mineral-amino acid preparates (39%), and this group was followed by antibacterials (26%) and antiparasitics (26%). The most observed adverse drug reactions were anaphylaxis and the local reactions on the injected region. Conclusion: It is confirmed that, a center where the adverse drug reaction reports could be evaluated and a spontaneous reporting system is needed. It is decided that it would be beneficial to report adverse drug reaction cases to the authorized veterinarians under circumstances of these cases.